Ritual Communication of Cheng Beng Ceremony on Chinese Ethnic in Balikpapan City - Lydia Tjioe; Gatut Priyowidodo; Felicia Goenawan (Journal of Content and Engagement, 2023)
This research was conducted to determine ritual communication in the Cheng Beng ceremony in the Chinese ethnic community. Ritual communication is unique and often difficult for individuals outside the community to understand. Like the Cheng Beng ceremonial ritual, this ritual is only understood by people who are ethnic Chinese. Communities can understand rituals on an ongoing basis both through coaching and discussion, this is what causes the understanding of the rituals of the Cheng Beng ceremony to be different from people outside the ethnic Chinese. The community studied is the ethnic Chinese community in Balikpapan City. This study uses a qualitative approach with ethnographic methods and data analysis using the QSR NVivo 12 computer program. The finding of the research indicate that the ritual communications used by the Chinese ethnic community in Balikpapan City in carrying out the Cheng Beng ceremony are communicative situations, communicative events, and communicative actions. In the communicative situation of the Cheng Beng ceremony, there are formal communicative situations and non-formal communication situations. In the communicative events of the Cheng Beng ceremony there are ritual agendas, ritual actors, and ritual equipment. In the communicative actions of the Cheng Beng ceremony, there are verbal actions and nonverbal actions. Ritual communication that occurs at the Cheng Beng ceremony for ethnic Chinese in Balikpapan City can occur by having ritual equipment that has meaning in everything that is prepared. The ritual equipment contained in the Cheng Beng ceremony will cause nonverbal actions. Then the ritual equipment and nonverbal actions of the Cheng Beng ceremony will give rise to non-formal communication situations. Limitations of the study in this study is the limited time in conducting field observations.